Undernutrition Affects the Occurence of Acute Respiratory Infections in Children under Five Years Old in Cipacing Rural - Windi Elsanita; Deni Kurniadi S; Diah Asri Wulandari; Elsa Pudji Setiawati (Faculty of Medicine Universitas Padjadjaran, 2015)
Background: Millennium Development Goals’ (MDGs) aims to decrease mortality in children will be achieved if the cause ofmortality include ARIs is eliminated. Acute respiratory infections are influenced by some factorssuch as nutritional status. The objective of this study was to analyze the correlation between nutritional status andthe occurrence of ARIs in children.Methods: This study used retrospective cohort approach during October─November 2012. One hundred and ten mothers with children under five years old with different nutritional status were randomly selected and then asked about their history of respiratory symptoms. Data were analyzed using chi square test.Results: About 66 under five children (60%) with good nutrition status had ARIs occurrence of <7 times and 5 children (4.5%) had ARIs≥7 times. In children with undernutrition, about 30 children (27.3%) had ARIs<7 times and 9 children (8.2%) had ARIs≥7 times. Bivariate analysis result showed that there was a correlation between nutritional status with the occurrence of ARIs in under five children (p<0.05).Conclusions: Acute respiratory tract infections are often experienced by undernutrition children. This study strengthens the essential to correct nutritional status to prevent the infections in children. DOI: 10.15850/amj.v2n3.497